USE OF SOLAR HEATING SYSTEMS AS AN ELEMENT OF A PASSIVE HOUSE (Academicia Globe: Inderscience Research, 2021)
This article analyzes the foreign experience of using energy efficient buildings in the construction. In particular, the prospects for the use of foreign experience in the conditions of Uzbekistan are sanctified, as well as the content and essence of the adopted normative legal acts for the development of this area, proposals and recommendations for improving this area are given.